Anomalous gas in ESO 149-G003: a MeerKAT-16 view. Issue 2 (21st December 2020) - Józsa, Gyula I G; Thorat, Kshitij; Kamphuis, Peter; Sebokolodi, Lerato; Maina, Eric K; Wang, Jing; Pieterse, Daniëlle L A; Groot, Paul; Ramaila, Athanaseus J T; Serra, Paolo; Andati, Lexy A L; de Blok, W J G; et al.
ABSTRACT: ESO 149-G003 is a close-by, isolated dwarf irregular galaxy. Previous observations with the ATCA indicated the presence of anomalous neutral hydrogen (HI ) deviating from the kinematics of a regularly rotating disc. We conducted follow-up observations with the MeerKAT radio telescope during the 16-dish Early Science programme as well as with the MeerLICHT optical telescope. Our more sensitive radio observations confirm the presence of anomalous gas in ESO 149-G003, and further confirm the formerly tentative detection of an extraplanar HI component in the galaxy. Employing a simple tilted-ring model, in which the kinematics is determined with only four parameters but including morphological asymmetries, we reproduce the galaxy's morphology, which shows a high degree of asymmetry. By comparing our model with the observed HI, we find that in our model, we cannot account for a significant (but not dominant) fraction of the gas. From the differences between our model and the observed data cube, we estimate that at least 7–8 per cent of the HI in the galaxy exhibits anomalous kinematics, while we estimate a minimum mass fraction of less than 1 per cent for the morphologically confirmed extraplanar component. We investigate a number of global scaling relations and find that, besides being gas-dominated with a neutral gas-to-stellar mass ratio of 1.7, the galaxy does not show any obvious global peculiarities. Given its isolation, as confirmed by optical observations, we conclude that the galaxy is likely currently acquiring neutral gas. It is either re-accreting gas expelled from the galaxy or accreting pristine intergalactic material.